Kemampuan Berbahasa Disabilitas Tunaganda pada Tiktok @Brandonsahcio: Perspektif Pembelajaran Tunaganda - Hapriyanto, Lasmana Fajar; Rosalia, Heppy Agi; Sitepu, Revita Inggeten Boru; Mintowati, Mintowati (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
This study aims to describe the language skills of a child with multiple disabilities, particularly speaking and listening skills, and to explain language learning and its development in cognitive and psychomotor aspects through TikTok as a social media platform. This study employs a descriptive qualitative approach using observation and note-taking techniques. The research subject is Brandon Sahcio, an individual with multiple disabilities experiencing intellectual disability and speech delay. The data sources consist of videos depicting language learning activities and social interactions uploaded on the TikTok account @brandonsahcio. The findings indicate that Brandon’s language abilities have shown gradual development over time. Language learning conducted through repetitive and contextual practices, supported by the family environment, has proven effective in improving speaking and listening skills. Development is evident not only in verbal communication but also in nonverbal communication and social interaction abilities. These findings suggest that cognitive limitations and speech delay do not entirely hinder children with multiple disabilities from developing language skills when consistent and meaningful stimulation is provided. This study concludes that social media can function as an informal language learning space that supports the communication development of children with multiple disabilities.